Applied complex training: An updated review and practical applications - Tredrea, M. S. J. (Journal of Australian Strength and Conditioning, 2017)
There is currently a wealth of information surrounding Complex Training (CT) and the mechanisms behind its performance effects. The ongoing research and education in this area continues to evolve and this review aimed to highlight the key areas of recent research to provide up to date guidelines for application of CT in athletic development programs. A search was conducted using Google Scholar with a filter applied to only include research conducted after 2004. Eleven studies were selected to be included in this review. The results of the combined studies demonstrate trends towards the use of high load, low repetition pre-loading protocols to enhance performance in athletic movements such as sprinting and jumping. These results provide the basis for current program design recommendations. Coaches should aim to select pre-loading exercises that best stimulate neural pathways and musculature used in the explosive movement with heavy loads between 80-95% 1RM. When prescribing repetition ranges for heavy pre-loading exercises, performing 2-6 reps is recommended with set ranges of 3-6 sets. These exercises should be followed by 8-minute rest periods to achieve optimal performance in singular events, and 4-5 minute rest intervals prescribed when employing antagonistic exercises in long-term training programs. When long-term training programs are employed, explosive or plyometric exercises should also be low volume in nature. Prescribing 1-3 maximal efforts after performing pre-loading exercises is recommended. Using alternating antagonistic style programming will allow for performance enhancements whilst simultaneously increasing efficiency of resistance training sessions.